2017
DOI: 10.1136/jnnp-2017-315971
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the geneLRP2increases relapse risk in multiple sclerosis

Abstract: The finding of a genetic locus that has extensive effects on neuronal development and repair is of interest as a potential modulator of MS disease course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…The MS susceptibility polymorphism within the Abelson Helper Integration site 1 gene ( AHI1 ) has been associated with higher relapse rate in two separate cohorts (one of children and another of adults), with similar effect size . In a genome wide search for alleles associated with relapse rate, a SNP within the gene LRP2 was associated with a twofold increase in the hazard to relapse in three independent MS cohorts, including adults and children . LRP2 is located on the cell surface of neurons and oligodendrocytes and participates in axon guidance.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%
“…The MS susceptibility polymorphism within the Abelson Helper Integration site 1 gene ( AHI1 ) has been associated with higher relapse rate in two separate cohorts (one of children and another of adults), with similar effect size . In a genome wide search for alleles associated with relapse rate, a SNP within the gene LRP2 was associated with a twofold increase in the hazard to relapse in three independent MS cohorts, including adults and children . LRP2 is located on the cell surface of neurons and oligodendrocytes and participates in axon guidance.…”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%
“…In this way, VD internalization can be mediated by LRP2, with or without the participation of CUBN and the DAB2 adaptor protein, although vitamin D also accesses some cells freely. Zhou et al () describe an association between MS relapses and LRP2 variant rs12988804. The study was based on data from three cohorts of patients with MS, including one series of paediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Genes influence everything in humans, including susceptibility to diseases such as MS. Genetic variations affect susceptibility to MS and MSR. Family studies have shown that MSR prevalence is ~15%, and that MSR risk may be higher among first-degree relatives compared with other family members, an effect that tends to decrease with “genetic distance.”[56] Several researchers have shown that there is a genetic contribution to MSR that varies among different populations. These efforts have led to the identification of >110 genes that have critical roles in the development and relapse of MS.[57]…”
Section: Effects Of Genes and The Environmentmentioning
confidence: 99%
“…Due to a lack of reliable longitudinal data and shortage of prospective studies on MSR, several investigations on the link between genetics and MSR have thus far failed to identify the factors that can reliably predict the risk of MSR at the genomic level. Zhou et al [56] undertook genome-wide association analyses in an attempt to identify different genetic variants that may influence and predict MSR. In total, they analyzed 449 DNA samples and clinical histories from various populations to determine the genetic differences that may influence MSR.…”
Section: Effects Of Genes and The Environmentmentioning
confidence: 99%